Structural and Spatial Development Study for TU Kemang Market in Bogor City - Lutfi, Muhamad; Syaiful, Syaiful; Chayati, Nurul; Wulandari, Retno Astri; Insan, Muhammad Khaerul (ASTONJADRO, 2026)
Kemang Market in Bogor City has a strategic role in the local economy, but its existing condition does not fully standard, with only 19 out of 35 facilities available. This condition results in a lack of convenience, accessibility, and operational efficiency in trading activities. In addition, the existing infrastructure has decreased in quality, especially in the sanitation system, drainage, and accessibility for people with disabilities. Therefore, re-planning was carried out to improve the quality of facilities and infrastructure with a more efficient spatial approach and structural analysis using the method Load and Resistance Factor Design (LRFD). This re-planning includes optimizing trade zoning, adding public facilities, improving the quality of sanitation, drainage systems, and applying tropical architecture concepts to support thermal comfort and natural lighting. The structural analysis results show that the main elements designed, namely WF 250.250.9.14 columns, WF 200.100.5.5.8 beams, and WF 300.150.6.5.9 roof trusses, have met safety standards and are able to withstand the planned loads. The estimated construction cost based on AHSP Cipta Karya, IDR 7,836,400,000.00. With this re-planning, Kemang Market is expected to transform into a more modern, orderly, safe, and national standard people's market, so as to increase operational effectiveness, the welfare of traders and visitors, and support local economic growth in a sustainable manner.